Mesoscale Auroral Curls in Antarctica - Xing‐Yu Li; Qiu‐Gang Zong; Ze‐Jun Hu; Yong‐Fu Wang; Jian‐Jun Liu; Xu‐Zhi Zhou; Chao Yue; Shan Wang; Zi‐Kang Xie; Xing‐Xin Zhao; Zhi‐Yang Liu; Ze‐Fan Yin; et al. (Geophysical Research Letters, 2024)
Abstract The morphology and motion of auroras have been widely studied due to their indications on magnetospheric processes. Here, we report a new kind of “auroral curls,” which have wavelengths in the mesoscale (∼100 km) and propagate azimuthally. Utilizing data from the Chinese Antarctic Zhongshan Station (the all‐sky imager and the high‐frequency radar), the Active Magnetosphere and Planetary Electrodynamics Response Experiment and the Defense Meteorological Satellite Program, we analyze an event occurred on 23 April 2019. We find these curls are fine structures in the poleward boundary of multiple arcs. Corresponding field‐aligned currents manifest as a series of longitudinally arranged pairs, while ionospheric flow velocities nearby oscillate with periods in the Pc 5 band. Observational evidence suggests these curls are connected with ultra‐low frequency (ULF) waves, which opens the possibility of using auroras to globally image ULF waves.